An evaluation of two government buildings in Quezon City with symptomatic sick building syndrome - Ayado, Denise P. (2007)
This study hopes to increase the awareness on health-affecting interiors, especially in the workplace, and the factors which can cause the occurrence of Sick Building Syndrome. It aims to assess the working environment of two government buildings, specifically the Bureau of Soils and Water Management, and the Bureau of Fisheries and Aquatic Resources. The study evaluated the occupants' environmental comfort, idetified typical SBS-related symptoms present among the occupants, and determined whether the level of satisfaction is related to the occurrence of symptoms among the buildings' occupants. Environmental comfort is based on the level of satisfaction with respect to noise, lighting, temperature, presence of odors, and the exposure of the individual to the workplace. The evaluation of the offices was done through a survey administered to one hundred randomly selected clerical employees, observation of the offices, and interviews with the service units responsible for the buildings' maintenance. Based on the findings, majority of the occupants from both buildings were satisfied with their working environment. However, there was a significant number of dissatisfaction in terms of the presence of odor in BSWM, inadequate lighting in BFR, and thermal discomfort in both offices. Also, there were a significant number of respondents exhibiting nasal, throat and eye symptoms, and symptoms of headaches. Still, the buildings cannot be considered to have SBS as the total number of cases among the respondents was not significant enough to consider the buildings as sick buildings.